TOURIST RESPONSES TO FLOWERING HILL ATTRACTIONS FACILITIES IN THE INDRAGIRI HILIR DISTRICTS - Rage Aprianto; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
A Responses result from an observation that is made upon a pacticular object or object and thus leads to a conclusion by each person to respond and object that is viewed, the response is divided in saveral forms such as question, apporal, objection, and opinion. Flowering hill attractions: 1) main facilities, 2) Support facilities, 3) complete facilities. The research is aimed : to know visitors responses to the facility on flowering hill atractions. The study uses qualitative descriptive method. With subiek of visitor research coming up on flower hill attractions. The data collection was by of questionnaires observation and documenting. Technomic data measurement uses the likert scale of data rating and withdrawal conclusion. And research shows that visitors responses to the facilities at the flower hill attractions in the Indragiri Hilir districts include the main facilities, the support facilities and complete facilities on the hill attraction are in good condition. keyword: primery facilities, support facilities, complete facilities.